Avoidance within a changing assessment paradigm for Mediterranean Hake stocks - RAGONESE, S. (Mediterranean Marine Science, 2009)
The Mediterranean hake Merluccius merluccius L., 1758, is the emblem of the so-called Mediterranean demersal fisheries paradox, showing a persistent, although stable, status of growth overexploitation and an impressive gap between current and any biological reference point. Almost full avoidance capability of large size females to bottom trawls, higher overall growth rates than previously believed and higher natural mortality in juveniles than adult, were considered among the most plausible explanation factors of such persistence. In the present note, arguments are illustrated to raise some concern about avoidance and highlight the important role of the other factors in improving assessments and launching a short term recovery plan for Mediterranean Hake stocks which is more acceptable to fishermen.